Peripheral Nerve Healing: So Near and Yet So Far - Baradaran, Aslan; El-Hawary, Hassan; Efanov, Johnny Ionut; Xu, Liqin (Seminars in Plastic Surgery, 2021)
Peripheral nerve injuries represent a considerable portion of chronic disability that especially affects the younger population. Prerequisites of proper peripheral nerve injury treatment include in-depth knowledge of the anatomy, pathophysiology, and options in surgical reconstruction. Our greater appreciation of nerve healing mechanisms and the development of different microsurgical techniques have significantly refined the outcomes in treatment for the past four decades. This work reviews the peripheral nerve regeneration process after an injury, provides an overview of various coaptation methods, and compares other available treatments such as autologous nerve graft, acellular nerve allograft, and synthetic nerve conduits. Furthermore, the formation of neuromas as well as their latest treatment options are discussed.
Keywords: peripheral nerve; injury; repair; review